MiR159 Represses a Constitutive Pathogen Defense Response in Tobacco. Issue 4 (10th February 2020) - Zheng, Zihui; Wang, Naiqi; Jalajakumari, Meachery; Blackman, Leila; Shen, Enhui; Verma, Saurabh; Wang, Ming-Bo; Millar, Anthony A.
Abstract : Repression of miR159 in tobacco triggers a constitutive defense response that confers immunity to Phytophthora parasitica. Abstract: MicroR159 (miR159) regulation of GAMYB expression is highly conserved in terrestrial plants; however, its functional role remains poorly understood. In Arabidopsis ( Arabidopsis thaliana ), although GAMYB-like genes are constitutively transcribed during vegetative growth, their effects are suppressed by strong and constitutive silencing by miR159. GAMYB expression occurs only if miR159 function is inhibited, which results in detrimental pleiotropic defects, questioning the purpose of the miR159- GAMYB pathway. Here, miR159 function was inhibited in tobacco ( Nicotiana tabacum ) and rice ( Oryza sativa ) using miRNA MIM159 technology. Similar to observations in Arabidopsis, inhibition of miR159 in tobacco and rice resulted in pleiotropic defects including stunted growth, implying functional conservation of the miR159- GAMYB pathway among angiosperms. In MIM159 tobacco, transcriptome profiling revealed that genes associated with defense and programmed cell death were strongly activated, including a suite of 22 PATHOGENESIS-RELATED PROTEIN ( PR ) genes that were 100- to 1, 000-fold upregulated. Constitutive expression of a miR159-resistant GAMYB transgene in tobacco resulted in phenotypes similar to that of MIM159 tobacco and activated PR gene expression, verifying the dependence of the above-mentioned changes on GAMYB expression. Consistent with the broad defense response, MIM159 tobacco appeared immune to Phytophthora infection. These findings suggest that the tobacco miR159- GAMYB pathway functions in the biotic defense response, which becomes activated upon miR159 inhibition. However, PR gene expression was not upregulated in Arabidopsis or rice when miR159 was inhibited, suggesting that miR159- GAMYB pathway functional differences exist between species, or factors in addition to miR159 inhibition are required in Arabidopsis and rice to activate this broad defense response.